An efficient model of load distribution for helical gears with modification and misalignment. (March 2018) - Peng, Yanjun; Zhao, Ning; Qiu, Pengyuan; Zhang, Mengqi; Li, Wang; Zhou, Ruchuan
Highlights: A load distribution model is proposed considering modifications and misalignments. High efficiency and good versatility are assured by a computational scheme. The method compares well with finite element analysis. Modifications, misalignments and input torque significantly affect load distribution. Abstract: An efficient model is introduced for evaluating the load distribution of helical gears, considering tooth modifications and misalignment errors. Instant contact points are obtained by unloaded meshing simulation. Combined with the full numerical method for elliptical Hertzian contact, the contact line under load is determined. Then the load distribution is derived from the minimization of potential energy. The proposed model is numerically implemented by a fixed-point iteration method based computational scheme, assuring high efficiency and superior versatility for tackling modifications and misalignments. And it is verified by finite element analysis. The effects of profile crowning, lead modification, misalignment and input torque on load distribution are investigated. Results indicate that contact pattern shrinks with increasing magnitude of profile crowning and decreasing input torque, resulting in abrupt load transitions between two and three meshing tooth pairs. While lead modification can transfer load from the edge of tooth surface to the center by inclining contact pattern to longitudinal direction, providing desirable load distribution. In addition, misalignment deviates contact pattern and sharing load respectively towards the ends of tooth profile and meshing cycle.